CLINICAL APPLICATION OF DIFFERENT CEREBRAL PROTECTION DEVICES IN CAROTID ANGIOPLASTY AND STENTING IN 1148 PATIENTS WITH CAROTID STENOSIS. (8th October 2012) - Hong, Yukun; Song, Zhiyuan; He, Guoxiang; Luxiang, Chi
Abstract : Objectives: To investigate the efficacy and safety of Carotid angioplasty and stenting (CAS) by different cerebral protection devices in 1148 patients with carotid stenosis. Methods: Carotid angioplasty and stenting by different cerebral protection device were performed in 1148 patients with carotid artery stenosis from April 2003 to June 2007. There were 812 males and 336 females in all patients. Age were from 56 to 84 (average 68±5). Transient ischaemia attach (TIA) occurred in 894 patients, and cerebral infarction (CI) occurred in 254 patients. 854 Angioguard (Cordis, Co.), 350 Spide (EV3, Co.), 25 Filterwire (Boston Scientific, Co.), 16 Emboshield (Abbott, Co.), 8 MoMa (Invetech, Co.) and 2 Aether (MicroPort, Co.) were used in CAS. Results: 1255 cerebral protection device were successfully placed in internal carotid arteries with 1148 patients, 8 MoMa were placed respectively in external and common carotid artery. Predilations were performed in 18 patients by Angioguard because of severe carotid stenosis. Cerebral protection device disrupture occurred in one patient during retrieve of Spide. The mean diameter of carotid stenosis was from (87.6±6.8)% to (18.9±10.8)% after CAS (p<0.01). no death and ischaemic stroke or cerebral arterial thrombosis occurred in 684 patients during 1 year of follow up. Conclusions: By option usage of cerebral protection device, CAS be successfully performed in patients with carotid stenosis, Mean while, CAS is a safe and effective method and improve cerebral ischaemia and prevent ischaemic stroke.